Effectiveness of Population Data Application Implementation in Kresek Village, Wungu Sub-District, Madiun Regency - Andi Rahman Putera; Eka Resty; Benny Agus S; Ilham Prihantono (IJISTECH (International Journal of Information System and Technology), 2018)
Population data processing conducted in Kresek Village, Wungu Sub-District, Madiun District is still manual. Data processing that has been used so far is the Excel application. This, causing data processing requires not a little time and quite a long time. With a system that has long data storage is not safe, especially in the long term. To overcome the problems related to population data, it is designed an application to process the data more easily and safely. The purpose of this study was to determine the effectiveness of the previously designed application of population data in Kresek Village. The study was conducted in Kresek Village, Wungu Sub-District, Madiun Regency. Respondents of this study were 2 Kresek Village officers as users. The analytical method used is descriptive analysis using data from interviews with respondents. Evaluation analysis is carried out to explain the new system that has been implemented. Based on the results of the study, it can be concluded that the application that has been designed is in accordance with the wishes of the Kresek village office. This application is able to ease the workload of village officials so that population data processing is more effective and efficient.